Penggunaan Tiktok Dalam Pendidikan Informal Dan Manfaatnya Bagi Mahasiswa Fakultas Dakwah Dan Komunikasi UIN Sumatera Utara - Ezra Muharrifah; Fadilla Hafizah; Faradiba Shaliha; Husnia Amro Br Sinaga; Irma Oktavia; Nur Azmi Fauzizah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
TikTok has become a popular platform among students, including those at the Faculty of Da'wah and Communication at UIN North Sumatra, for use in informal educational contexts. This research aims to investigate how TikTok is used as an informal educational tool by students at the faculty. The research method used is a case study with a qualitative skills, and broaden horizons about da'wah and communication in contemporary contexts.Benefits include facilitating independent learning, building informal learning communities, and promoting creativityamong students.